Effect of additional strengthening of colonic anastomosis on abdominal contamination severity - M. M. Mylytsia; К. M. Mylytsia; V. V. Steblianko; V. V. Soldusova; V. S. Kazakov (Сучасні медичні технології)
Purpose of the study. To investigate the effect of additional strengthening of the colonic anastomosis (CA) using modern adhesive materials on the severity of abdominal contamination in patients with insulin resistance (IR).